Protective effect of autologous adipose-derived mesenchymal stem cells on renal ischemia reperfusion injury - HUANG Ke-jing; HUANG Ting; HU Wen-bing; XIANG Li-na (Linchuang shenzangbing zazhi)
Objective To observe the protective effects of tail veil injection of autologous adipose-derived mesenchymal stem cells(ADMSCs) on the renal ischemia reperfusion(IR) injury of rats.Methods Adult male Sprague-Dawley(SD) rats(n = 24) were equally randomized into sham operation group(sham control),IR injury model group(IR plus saline only),and cell therapy group(IR plus intravenous administration of 1.OX 106 autologous ADMSCs),n = 8 each group.Fourteen days before IR,the adipose tissue around the greater omentum was cut for the preparation of ADMSCs.Twentyfour h before modeling,serum creatinine,urine volume and urinary albumin/creatinine ratio were evaluated as blank controls.The renal IR injury model was set up.In the sham group,the middle incision was cut and sutured.One h after IR,ADMSCs were transplanted through tail vein of rats in cell therapy group,and the same volume of normal saline was injected into the rats of sham operation group and model group.The renal functional indexes including serum creatinine,urine volume and urinary albumin/creatinine ratio were detected by biochemical method 24 h and 72 h after IR.The pathological changes were observed by HE staining,and the relative expression of HO-1 and NQO-1 was detected by Western blotting.Results The results of biochemical detection(serum creatinine and urinary albumin/creatinine ratio) showed that the kidney function of rats in cell therapy group was significantly better than in model group(P<0.05).The histopathological observation showed that the obvious morphological damage was observed in the renal tubule in model group,and amelioration was observed in cell therapy group.Western blotting showed notably higher expression of NAD(P) H quinone oxidoreductase KNQO1 and HOI proteins,two indicators of anti-oxidative capacity,in cell therapy group than in model group.Conclusions ADMSCs therapy minimized kidney damage after IR injury through suppressing oxidative stress.